Diaryliodonium salts as hydrosilylation initiators for the surface functionalization of silicon nanomaterials and their collaborative effect as ring opening polymerization initiators. Issue 23 (2nd June 2017) - Helbich, T.; Kloberg, M. J.; Sinelnikov, R.; Lyuleeva, A.; Veinot, J. G. C.; Rieger, B.
Abstract : Diaryliodonium salts were found to initiate hydrosilylation reactions on the surface of silicon nanosheets as well as silicon nanocrystals of different sizes. Abstract : Diaryliodonium salts were found to initiate hydrosilylation reactions on the surface of silicon nanosheets as well as silicon nanocrystals of different sizes. A variety of different functional substrates can be used to stabilize the surface of the photoluminescent materials. Additionally, the combination of hydride terminated silicon nanomaterials with diaryliodonium salts was found to initiate cationic ring opening polymerization, demonstrating the potential of silicon based nanomaterials as coinitiators and enabling a mild, straightforward reaction method.